A multi-case study of the implementation of an integrated approach to safety in small enterprises. (January 2015) - Nielsen, K.J.; Kines, P.; Pedersen, L.M.; Andersen, L.P.; Andersen, D.R.
Highlights: An integrated behavior/culture-based intervention implemented in small enterprises. A quasi-experimental, multi-case design with two intervention and two control enterprises. The intervention was a success in one of the interventions enterprise, but not the other. No improvement in the controls. The intervention effectuated problem solving and culture change as measured here. Abstract: An integrative approach to managing safety has been proposed which is based on a combination of the behavior change and culture change approach to safety. The key features are a data-based and participatory problem-solving process and an explicit culture change process. Objective : The aim of the current study was to operationalize and test the implementation of an integrative approach to safety in small (20–49 employees) enterprises within the metal and wood processing industries using a quasi-experimental, multi-case design with two intervention (Int1 and Int2) and two control enterprises Methods : Baseline measures included safety observations, questionnaires, interviews and inspection of machine safety. The intervention consisted of workshops where the safety organization, workers and supervisors discussed safety issues identified at baseline (the problem solving process), and a workshop on safety management and leadership, followed by several individual safety coaching sessions with supervisors (the culture change process). Results : The results differed between the two intervention enterprises. In Int1 supervisors performed 80% of the activities planned in the coaching sessions, and 74% of the activities from the worker workshops, and 82% of the activities from the safety organization workshop were resolved, compared to only 48%, 59% and 20% respectively in Int2. Interviews with management and workers indicated a difference in management commitment to the process in the enterprises, and a lack of trust and perceived reciprocity between workers and supervisors in Int2. The effect measures showed improved safety leadership, safety knowledge, safety involvement and machine safety in Int1 at follow-up, and no improvements in Int2, as was also the case for the two control enterprises. The results show that it is possible to implement the approach successfully in small enterprises, although further and lengthier studies are needed to link the approach to culture change. It is crucial to ensure management commitment throughout the implementation.